Analisis Konten Edukasi Kesehatan pada Akun Instagram @dokterbrando.spy dalam Meningkatkan Literasi Kesehatan Masyarakat - Veriyady, Eka; Muhammad Najih Farihanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The purpose of this study is to analyze health education content on the Instagram account @dokterbrando.spy and to examine its potential in improving public health literacy. The method used in this research is qualitative content analysis of seven health education posts with the highest level of interaction. Data collection techniques were conducted through observation and documentation of video/Reels content and audience interactions. The results show that all content uses a non-conventional language style that tends to be harsh and expressive as the account’s distinctive characteristic, while still focusing on delivering health education information. The high level of audience interaction indicates that this communication style is effective in attracting attention and encouraging audience engagement. The conclusion of this study is that the Instagram account @dokterbrando.spy has the potential to contribute to improving public health literacy through a communication approach that aligns with the characteristics of social media. Keywords: Content Analysis, Health Education, Health Literacy, Instagram.